The EFFECT OF HEALTH EDUCATION WITH ONLINE METHODS ON KNOWLEDGE ABOUT COVID-19 IN ADOLESCENTS: EFFECT OF HEALTH EDUCATION WITH ONLINE METHODS ON KNOWLEDGE ABOUT COVID-19 IN ADOLESCENTS - Sari, Gevi Melliya; Puspita, Sylvie; Kusyani, Asri (WELL BEING, 2022)
The Covid-19 case in Indonesia shocked the community and caused fear from various groups. Transmission of this virus occurs through droplets or body fluids splashed on a person or objects around them that are 1-2 meters away through coughing and sneezing. Community knowledge is very influential in behavior in carrying out prevention. The purpose of this study was to determine the effect of health education using online methods on knowledge about Covid-19 in adolescents. The research design was pre-experimental with a one-group pretest-posttest design approach. The population is 131 respondents. The sampling technique used is purposive sampling. The variables in this study are health education about Covid-19 as the independent variable and knowledge about Covid-19 as the dependent variable. Data collection used a questionnaire and data analysis using the Wilcoxon test. The results showed that before being given health education, most of the respondents had sufficient knowledge, namely as many as 74 respondents (56.5%), then after being given health education, almost all respondents had good knowledge, namely as many as 122 respondents (93.1%). The results of data analysis using the Wilcoxon test showed a sig (2-tailed) p-value: of 0.000 and an error rate of P< 0.05, meaning that there is an effect of online health education on knowledge about Covid-19 in adolescents. Providing health education using online methods about Covid-19 increases understanding of the state of the Covid-19 pandemic. It is hoped that this increased knowledge will allow youth to implement health protocols as well as possible so that it becomes an effort to reduce Covid-19. Teenagers are expected to always implement health protocols such as: wearing masks, washing hands with soap, keeping their distance, and so on, this is done to prevent transmission of the virus. Keywords: Health Education, Online, Knowledge, Covid-19, Adolescents